Rural students' pathways to higher tertiary education in Zimbabwe: Overcoming barriers, promoting inclusion and success - Nowell Chidakwa (Interdisciplinary Journal of Rural and Community Studies, 2025)
Accessing higher tertiary education for rural students in Zimbabwe is a complex journey shaped by various socio-economic, cultural, and geographic factors unique to their circumstances. This study examines the experiences of rural students in accessing, participating in, and attaining higher tertiary education through the lens of Freire's theory of critical consciousness. It employs a critical emancipatory research paradigm, utilising participatory action research methodologies. Twenty participants were purposively selected and actively involved as co-researchers throughout the research process to identify empowering practices that can transform their educational realities. Data was collected using focus group discussions and Photovoice, allowing participants to share narratives and visually represent the barriers in their educational journeys. Critical discourse analysis revealed various factors that shape educational trajectories, such as geographic isolation, financial constraints, a lack of collegiate guidance, and the internalisation of negative perceptions about rural identities. Findings also highlighted protective factors, including strong family and community support systems, self-determined mindsets, and engagement with college-bridging programmes. Through critical dialogues, participants explored ways to challenge internalised stigmas and develop critical literacies to navigate systemic barriers. The PAR process enhanced participants' critical consciousness and enabled them to collectively generate rural student-led solutions for equitable educational access. The importance of adopting strengths-based and culturally sustaining approaches that amplify the voices of rural students in transforming policies and practices was highlighted. Importantly, this study demonstrated the emancipatory potential of PAR in fostering resilience and self-advocacy among rural students, thereby promoting higher tertiary education as a means for social and economic mobility.